China-Latin America and the Caribbean Relationships: History, Aspects and Implications - Hernández, Emilio (Sinología hispánica. China Studies Review, 2019)
According to reports from the International Monetary Fund (IMF), in 2014, China became the first world power ousting the United States. This growth implies the need for access to a large amount of energy resources and raw materials. While in the past China was able to be self-sufficient, this is now impossible because the difference between what China consumes and what it produces is widening. For this reason, it is necessary for Beijing to carry out foreign relationships and policies that will enable it to meet its own needs. It is in Africa and in Latin America and the Caribbean where, over the last few decades, China has focused and directed its foreign policy. The aim of this paper is to provide a historical overview of the relations between China and Latin America and the Caribbean, to analyze the different aspects into which they are divided, to identify similarities and differences between China’s relationships with Africa and with Latin America and to assess the implications that these relationships could have for other countries and regions of the world.